Perceived barriers and enablers to outdoor mobility among older adults in the Nordic Arctic Region - Anastasia; Agneta; Steinunn; Arja (Magyar Gerontológia, 2025)
Little is known how older people move outdoors in the Arctic region, challenged by long and snowy winters, vast distances, underdeveloped transportation systems, and remote community facilities.